Hubungan Antara Kepuasan Pelanggan Terhadap Kualiti Dan Harga Barangan Cenderamata Di Kuching, Sarawak - SAFURA, BINTI ABU SAMAH (Universiti Malaysia Sarawak(SARAWAK), 2018)
Customer satisfaction is an important issue to ensure the convenience of customers in an organization. This is because the quality of products or services provided by an organization can be evaluated and improved based on the views gained from the customers. The objective of this study is to analyze the relationship between customer satisfaction on the quality and prices of souvenir items in Kuching, Sarawak. This study will involve foreign and local tourists. The research design is a survey using a quantitative approach. Instruments used are through the survey form. Questionnaire was distributed to a total of 250 respondents. The data obtained were analyzed using Social Science Statistics Package (SPSS). The findings show the level of customer satisfaction on the quality and prices of souvenir items in Kuching, Sarawak.